STUDY OF RAW MATERIAL RESOURCES FOR THE PRODUCTION OF ALUMINOSILICATE BINDERS UNDER THE CONDITIONS OF THE ARAL SEA REGION - Sabirova F. R.; Ruzmetova A. Sh.; Matchanov Sh. K. (Modern American Journals, 2025)
This paper presents a study of local raw materials from the Aral Sea region aimed at producing aluminosilicate binders. The mineralogical and chemical composition, as well as the physical and technological properties of natural resources such as kaolin, limestone, and brick factory waste (chamotte scrap), were examined. The obtained results indicate the potential for efficient use of local mineral resources in the Aral region as a basis for environmentally friendly and economically viable aluminosilicate binders, which contributes to sustainable natural resource management and the development of the region’s construction industry.
Keywords: Aluminosilicate binders, Aral region, kaolin, chamotte scrap, mineral raw materials.